Front Cover: Revisiting the Electrochemical Lithiation Mechanism of Aluminum and the Role of Li‐rich Phases (Li1+xAl) on Capacity Fading (ChemSusChem 12/2019). Issue 12 (24th June 2019) - Qin, Bingsheng; Diemant, Thomas; Zhang, Huang; Hoefling, Alexander; Behm, R. Jürgen; Tübke, Jens; Varzi, Alberto; Passerini, Stefano
Abstract : The Front Cover shows the complexity and puzzling of the Li‐alloying mechanism in aluminum electrodes. The reaction mechanism is revisited by combining a number of complementary in situ and ex situ techniques, thereby gaining new insights on phase transitions, electrode kinetics, and surface chemistry. Interestingly, Li‐rich alloys (Li1+ x Al) are not only formed upon deep lithiation but are also always present on the electrode surface. In addition, the growth of such phase in the electrode bulk is found to be strictly correlated with cell failure. Finally, the ionic liquid‐based electrolyte (0.2m LiTFSI in Py14 TFSI) delays the occurrence of this phenomenon compared with conventional organic electrolyte (1m LiPF6 in EC/DMC), resulting in an improved cycling stability. More information can be found in the Full Paper by Qin et al. on page 2609 in Issue 12, 2018 (DOI: 10.1002/cssc.201900597 ).